1990
DOI: 10.1128/jcm.28.5.1039-1046.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and description of "Campylobacter upsaliensis" isolated from human feces

Abstract: During a 3-year period, "Campylobacter upsaliensis" was isolated from 99 patients. Phenotypic characterization and numerical analysis of protein electrophoregrams showed evidence that "C. upsaliensis" is a distinct Campylobacter species with unique characteristics. The MBCs of 13 antibiotics were determined. In general, these organisms were highly susceptible to drugs that were present in the selective isolation media, making none of the available selective media suitable for the isolation of "C. upsaliensis."… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(20 citation statements)
references
References 37 publications
0
18
1
1
Order By: Relevance
“…Plasmid profiling alone cannot be regarded as a primary typing option for C. upsaliensis, since only about half (42 of 98) of the strains, irrespective of the animal host, carried plasmids. This frequency is lower than that found in previous studies (7,17), and the difference may be due to the fact that those studies were based on strains predominantly of human origin. Five of the 11 16S ribotypes did not contain plasmid-bearing strains.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Plasmid profiling alone cannot be regarded as a primary typing option for C. upsaliensis, since only about half (42 of 98) of the strains, irrespective of the animal host, carried plasmids. This frequency is lower than that found in previous studies (7,17), and the difference may be due to the fact that those studies were based on strains predominantly of human origin. Five of the 11 16S ribotypes did not contain plasmid-bearing strains.…”
Section: Discussioncontrasting
confidence: 77%
“…Plasmid profile typing has been shown to be relevant in the study of C. upsaliensis (4,7,12,17). Owen and Hernandez (17) detected extrachromosomal DNAs in 87% of strains, observing fifteen different plasmid profiles and an association of plasmid profile with geographical area of strain origin.…”
mentioning
confidence: 99%
“…upsaliensis is highly prevalent in dogs and cats and very rarely observed in other sources; hence, pets may be a source of infection that humans are frequently exposed to. Campylobacter upsaliensis is among the leading emerging Campylobacter pathogens and, with suitable culture methods, isolation rates higher than those of C. coli were reported in patients with gastroenteritis in Europe (Goossens et al., ; Lindblom et al., ), Africa (Lastovica, ) and North America (Labarca et al., ). In New Zealand, a recent survey of laboratory practices showed none of the public health laboratories used culture methods suitable for detection of non‐ jejuni/coli Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…were isolated from both diarrhoeic and asymptomatic dogs using a passing filtration technique (Sandstedt et al 1983). Since then other reports have described the isolation of these organisms and have suggested they are potential human pathogens associated with enteritis and bacteraemia, and also opportunist infections in immunocompromised individuals (Steele et al 1985 ;Lastovica et al 1989;Patton et al 1989;Taylor et al 1989;Chusid et al 1990;Goossens et al 1990). In 1991 DNA hybridization studies showed that this group of organisms belonged to a new species and the name Campylobacter upsalienszs was proposed (Sandstedt and Ursing 1991).…”
Section: Introductionmentioning
confidence: 99%